2001
DOI: 10.1071/rd01082
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and sex education for young people in China

Abstract: Although China has had a rich sexual culture for thousands of years, Chinese people are usually unwilling to openly discuss issues of sex. Some parents are quite ignorant of the change in their children's sexual attitude and behaviour. In China today, adolescents are becoming much more sexually liberated. Premarital sex and unplanned pregnancies among teenagers are increasing. Sexually transmitted diseases (STD) including HIV/AIDS are also spreading rapidly. However, young people lack basic information on AIDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 2 publications
1
52
0
Order By: Relevance
“…[13][14][15] There is a limited formal sex education component in the Chinese school curriculum, and communication between students and their school teachers or parents regarding sex education is also limited. 16,17 Lack of appropriate sex education in schools and homes may drive students to seek information about sex online. For example, studies among Chinese college students found that the Internet has been considered as one of the major sources of sexual information, especially among male students.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] There is a limited formal sex education component in the Chinese school curriculum, and communication between students and their school teachers or parents regarding sex education is also limited. 16,17 Lack of appropriate sex education in schools and homes may drive students to seek information about sex online. For example, studies among Chinese college students found that the Internet has been considered as one of the major sources of sexual information, especially among male students.…”
Section: Introductionmentioning
confidence: 99%
“…Homosexual practices or multiple sexual partners have been disdained by mainstream society (Zhang et al, 1999). Following centuries of silence on the subject, only in very recent years has sex education been addressed in the school curriculum (Gao et al, 2001). Although premarital sex, extramarital sex, and prostitution are strongly denounced by traditional Chinese cultures, the population is becoming more tolerant of these activities and their prevalence is rapidly increasing (Gao et al, 2001;Zhang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Since the implementation of the "open-door" policy in China in the 1970s, and especially since the economic reforms of the middle of 1980s, sexual behaviors and attitudes have been undergoing significant change in China, especially among the young population (Gao et al, 2001;Zhang et al, 1999). In traditional Chinese society, a woman is expected to remain virginal until her wedding night and to remain faithful to her husband throughout her life.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, 28% of the Euro-Canadian and 37.8% of the East Asian women participated in the psychophysiological testing. There is a wealth of research showing that individuals of East Asian descent hold sexually conservative attitudes by Western norms (Gao, Lu, Shi, Sun, & Cai, 2001;Higgins & Sun, 2007;Higgins et al, 2002). This robust result, in conjunction with the well-documented finding that East Asian women are more reluctant than Euro-Canadian women to undergo Pap testing (Hislop, Teh, Lai, Labo, & Taylor, 2000;Hislop et al, 2004;Kagawa-Singer & Pourat, 2000), seems contradictory to this finding that the East Asian women were more likely to participate in a physically invasive research procedure.…”
Section: Self-identified Ethnic Group (East Asian Vs Eurocanadian) Amentioning
confidence: 96%